Romantic Scepticism and the Descent into Nihilism in T.S. Eliot's 'Burnt Norton'. (2nd January 2017) - Cauchi, Francesca
ABSTRACT: The nihilism consequent upon the First World War, and which T.S. Eliot's Four Quartets sought in some measure to dispel, emerges in 'Burnt Norton' as the chilling culmination of a putatively redemptive idealism. In common with his Romantic forebears, Wordsworth and Coleridge in particular, the ambivalent narrator of Eliot's first quartet harbours a desire to transcend the limits of temporality through the positing of an ideal world that he suspects may be illusory. The result is a descent into nihilism as extreme as it is absolute: a nihilism which Nietzsche fifty years earlier had decried as a 'will to nothingness.'